An Empirical Study of Audit Committee Support for Auditors Involved in Technical Disputes with Client Management. - Knapp, Michael C. (The Accounting Review, 1987)
ABSTRACT: Critics allege that audit committees often fail to mitigate management pressure on auditors when disputes arise during an audit. The objective of this study is to investigate factors that may affect the likelihood that audit committees will support auditors, rather than management, in audit disputes. A repeated measures experiment was conducted using 179 audit committee members as subjects. Analysis of variance results show that backgrounds of audit committee members may be predictive of their willingness to support auditors involved in disputes with client management. Also, two contextual variables seem important–whether the relevant professional standards are objective and the relative financial condition of the audited firm.